The Effect of a Summer Camp Intervention on the Nutrition Knowledge and Dietary Behavior of Adolescent Girls. Issue 4 (July 2016) - Jennings, Leah; Nepocatych, Svetlana; Ketcham, Caroline; Duffy, Diane
The purpose of this study was to design a rewards-based nutrition intervention program to improve knowledge and dietary behaviors of adolescent girls. Our participants consisted of eight girls ages 11 to 13 years. Nutritional knowledge was assessed before and after intervention program through a "Jeopardy" style quiz game and posttest questionnaires. Participants were also interviewed throughout the week about typical dietary behaviors, daily physical activity, and self-esteem. Educational activities took place for 2 to 3 hours each day and included a grocery store scavenger hunt, healthy baking demonstrations, and relay races. Participants received bracelets and charms as rewards for participation in activities. Nutritional knowledge increased for six out of eight participants, although the overall increase was not found to be statistically significant ( p = .20). Significant correlations were found between measures including dietary behavior (soda consumption per week and perceived importance of body weight: r = −.827, p = .01), self-esteem (weight and endurance: r = .801, p = .03), and fitness levels (weight and curl-ups completed in 30 seconds: r = −.729, p = .04). This study shows promising evidence that this nutrition education intervention could be effective at increasing nutrition knowledge, thus potentially affecting future dietary behaviors of adolescent girls.